Tailoring Borate Mediator Species Enables Industrial CO Production with Improved Overall Energy Efficiency by Sustainable Molten Salt CO2 Electrolysis - Xinyu Li; Bowen Deng; Kaifa Du; Wenmiao Li; Di Chen; Xin Qu; Fangzhao Pang; Xiaodan Zhang; Hao Zha; Huayi Yin; Dihua Wang (Advanced Science)
Abstract The electrochemical conversion of CO2 into CO represents a promising strategy for mitigating excessive global greenhouse gas emissions. Nevertheless, achieving industrial‐scale electrochemical CO2‐to‐CO conversion with enhanced selectivity and reduced energy consumption presents significant challenges. In this study, a borate‐enhanced molten salt process for CO2 capture and electrochemical transformation is employed, achieving over 98% selectivity for CO and over 55% energy efficiency without the necessity for complex and costly electrocatalysts. Cathodic CO2 electro‐reduction (CO2ER) with the anodic oxygen evolution reaction (OER) at an overall current density of 500 mA cm−2 using non‐nanostructured transition‐metal plate electrodes at 650 °C is coupled. By regulating the electrolyte's oxo‐basicity with earth‐abundant borax (Na2B4O7), a borate‐enhanced electrolyte is established that accelerates the overall electrochemical reaction efficiently. This system involved a series of well‐designed target borate species (BO33−, BO2−, and B4O72−) that acted as mediators shuttling between the cathode and anode, favoring CO as the primary cathodic product. Manipulating the atmosphere above the anode facilitated a spontaneous transformation of borates, further enhancing OER performance with long‐term operational stability over a cumulative period of 50 h, while also reducing overall energy consumption. This work presents a cost‐effective strategy for the industrial‐scale production of CO derived from CO2, contributing to a lower carbon footprint by establishing a sustainable borate‐mediated closed loop.